Coupling Effect of Creep Deformation and Prestress Loss of Anchored Jointed Rock. (10th September 2020) - Zhu, Bairu; Song, Yang; Wang, Heping; Li, Yongqi
Abstract : To explore the variation behaviour of anchor jointed rock subject to high in situ stress states, a coupling effect calculation model based on stress equality was established based on the original rheological model of rock by combining element combination theory and experiment, and the model was verified. The coupling effect between rock mass creep and bolt prestress loss is established by setting the deterioration function of bolt prestress loss. The uniaxial creep test is performed on specimens with different joint angles, and the results show that the prestress loss time in anchor rods decreases linearly with increasing stress level. With increasing stress level, the time of prestress loss decreases linearly with the increase in stress level. With increasing axial load, the deformation caused by the transverse expansion stress of the specimen can offset the compression deformation of the prestressed anchor rod. The relationship between prestress loss in anchors and creep of rock is solved theoretically, and the stability criterion for anchor jointed rock is proposed. The results of this study provide a scientific reference for anchor design of deep jointed rock mass.